Strategi Peningkatan Loyalitas Pelanggan Shopee di Kota Jambi: Evaluasi Harga, Promosi, dan Kepuasan - Hassandi, Irfan; Effiyaldi, Effiyaldi; Pebriyanto, Feri; Hidayat, Teguh (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This study aims to find out how much influence price; promotion and satisfaction have on customer loyalty of e-commerce shopee in Jambi city. The method used in conducting the analysis is a quantitative approach. The object of this study is customers who have made transactions through e-commerce shopee in Jambi city. The number of samples to be used is 100 respondents. The results of the observation illustrate that price has a significant and positive impact on increasing customer loyalty with a significance value of 0.041. Promotion has a significant and positive impact on increasing customer loyalty with a significance value of 0.022. Satisfaction also has a significant and positive impact on increasing customer loyalty with a significance value of 0.000. In addition, price, promotion and customer satisfaction simultaneously have a significant and positive impact on increasing customer loyalty with a significance value of 0.000.